CASE MANAGEMENT BASED ON THE PREVENTION OF GENDER–BASED VIOLENCE IN THE PROVISION OF ANTENATAL CARE TO PREGNANT WOMEN AND THE MANAGEMENT OF REPRODUCTIVE HEALTH CARE FOR WOMEN OF CHILDBEARING AGE - Allamuratova Ulguzi Djumaevna; Ziyoev Abdisalom Mardonovich; Abdullaev Abdug'affor Mamatqosimovich; Xurramov Eldor Panjievich; Valieva Dilbar Axmedovna (Web of Journals Publishing, 2024)
In the article, the issues of strengthening the reproductive health of the population, maintaining the statistical indicators of women of childbearing age in an embodied/integrated manner, reducing maternal and infant mortality through regular case management, and protecting motherhood and childhood are discussed. This case–management healthcare system is intended for primary midwives, patronage nurses, heads of OP/OShP, KTPP, UASh specialists, reproductive specialists, internal pharmacy managers, chief specialists of district and city OB and BMQ, chief obstetrician–gynecologists and specialists of regional OB and BMQ management. and intended for social workers.
Keywords: case management, antenatal care, integration, contraception, vertical lines, regionalization, gender violence, sexual exploitation, oppression and violence, social service, rehabilitation center, shelter, victimization, autoaggression, rumination.